Arterial hypertension in children with hemolytic uremic syndrome after kidney transplantation. (13th June 2015) - Hoenecke, Johannes; Hartmann, Hans; Melk, Anette
Abstract The development of arterial hypertension after KTX is a well‐known complication. HUS is a systemic disease associated with arterial hypertension during long‐term follow‐up. Our goal was to report on the severity of arterial hypertension after KTX in patients with typical and atypical HUS. We analyzed the course of 197 patients with HUS, of which 22 (n = 10 with typical HUS; n = 12 with atypical HUS) developed ESRF and received KTX as renal replacement therapy. We analyzed data from 1766 casual BP and 85 24‐h ABPM measurements. In addition, we evaluated the used antihypertensive strategy. Comparison between the two patient groups revealed that patients with atypical HUS had significantly higher casual SBP‐SDS and DBP‐SDS values after KTX despite similar intensity of antihypertensive treatment. These data were supported by analysis of ABPM profiles showing comparable results for the interval 1–5 yr after KTX. Patients with atypical HUS had a greater severity of arterial hypertension despite similar treatment strategies and intensity of treatment. Our observation, even though in a small cohort, supports recent genetic studies showing arterial hypertension closely associated with HUS‐causing mutations in patients with atypical HUS.